Effect of Timing and Duration of Non-Invasive Ventilation on Outcomes in Acute Exacerbation of COPD: A Prospective Study from Nepal (Birat Journal of Health Sciences, 2025)
Introduction: Acute exacerbation of chronic obstructive pulmonary disease is a major cause of hospital admissions and mortality among patients with COPD, particularly in low- and middle-income countries. Non-invasive positive pressure ventilation is a cornerstone in the management of AECOPD with type 2 respiratory failure, shown to reduce intubation rates and mortality. However, clinical outcomes may depend on factors such as timing of initiation, ventilatory pressures, and duration of therapy, which remain underexplored in South Asian settings.Objective: To evaluate the effect of timing and duration of NIPPV on clinical outcomes among patients admitted with AECOPD and type 2 respiratory failure at a tertiary care hospital in Nepal.Methodology: A prospective observational cohort study was conducted among 246 AECOPD patients requiring NIPPV at Tribhuvan University Teaching Hospital, Kathmandu. Data on time to NIPPV initiation, pressure settings, session duration, and total NIPPV use were collected. The primary outcome was NIPPV success or failure (defined as need for invasive ventilation or in-hospital death). Statistical analyses included t-test, Mann-Whitney U, and Chi-square tests with significance at p < 0.05.Results: Of 246 patients, 208 (84.6%) had successful NIPPV outcomes. Early initiation ( 0.05). Mean IPAP was significantly higher in the failure group (15.5 ± 1.0 cm H₂O) than in the success group (13.9 ± 2.4 cm H₂O, p < 0.0001).Conclusion: Early initiation and optimal pressure titration of NIPPV are associated with improved outcomes in AECOPD with type 2 respiratory failure. Excessively high inspiratory pressures and delayed response predict longer hospitalization and higher failure rates.